2017
DOI: 10.1371/journal.pone.0174354
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in first and secondhand smoke exposure, spirometric lung function and cardiometabolic health in the old order Amish: A novel population without female smoking

Abstract: Due to their relatively homogeneous lifestyle and living environment, the Amish offer a novel opportunity to study the health associations of tobacco smoke exposure, particularly secondhand smoke. We hypothesized that secondhand smoke exposure is associated with worse pulmonary and cardiometabolic health. We examined cross-sectional data on 3568 Amish study participants, including tobacco use and secondhand smoke exposure from family members included in the study. Thirty-four percent of Amish men reported ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…A study from China assessed lung function among 1033 adults aged 40–69 years and included both ever- and never-smokers, and found a reduction in lung function associated with SHS among women only [ 6 ]. A recent study among 3568 old-order Amish in the U.S. found that exposure to second-hand tobacco smoke was associated with a 2.7% lower forced expiratory volume in 1 sec (FEV 1 ) percentage in women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from China assessed lung function among 1033 adults aged 40–69 years and included both ever- and never-smokers, and found a reduction in lung function associated with SHS among women only [ 6 ]. A recent study among 3568 old-order Amish in the U.S. found that exposure to second-hand tobacco smoke was associated with a 2.7% lower forced expiratory volume in 1 sec (FEV 1 ) percentage in women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…ETS exposure in non-smokers has also increased mortality from lung cancer and COPD [33,34]. Additionally, ETS has been associated with a greater burden of cardiovascular risk factors [35], such as higher BMI and fasting glucose [36], and with endothelial dysfunction and increased plasma fibrinogen levels [37].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be associated with differences in the quantity of smoking between the two sexes. Notably, numerous previous studies revealed sex differences in the effect of smoking on metabolic parameters (50)(51)(52). One longitudinal study of non-diabetic individuals demonstrated that smoking was associated with improved insulin sensitivity in women, but reduced insulin sensitivity in men (50).…”
Section: Discussionmentioning
confidence: 99%
“…Reed et al (51) reported the association of passive smoking with greater BMIs and fasting plasma glucose levels in men, and with reduced HDL-cholesterol levels in women among the Old Order Amish population. In late adolescence, passive smoking was also associated with lower HDL-cholesterol in girls, demonstrating a sex difference in the findings (52).…”
Section: Discussionmentioning
confidence: 99%